Deciphering the photocurrent polarity of Bi2O2Se heterojunction phototransistors to enhance detection performance. Issue 25 (8th June 2021) - Han, Jiayue; Han, Xingwei; Zhang, Chaoyi; Peng, Silu; Han, Chao; Zhang, Xingchao; Liu, Xianchao; Du, Xiaoyang; Gou, Jun; Wang, Jun
Abstract : By incorporating C60 into graphene/Bi2 O2 Se, graphene/C60 /Bi2 O2 Se and show good performance at communication band (1310 and 1550 nm) with four different type power dependent polarity photocurrents. Abstract : With the emergence of bismuth-based oxychalcogenide materials, Bi2 O2 Se shows superiority in photodetection owing to its favorable mobility and air stability. Nevertheless, the photodetection performance is limited by its low bandgap and extinction coefficient in the near-infrared region. Here, by stacking C60 /Bi2 O2 Se heterojunction onto graphene with a symmetrical electrode, we observed distinctive polarity variation in the broadband photocurrents (488–1550 nm) owing to the wavelength-dependent band alignment. Meanwhile, the all-negative polarity responses of graphene/Bi2 O2 Se demonstrate high photo-responsivity (∼7160 A W −1 ) with 1.7 × 10 6 % external quantum efficiency, fast speed down to 57 μs and detectivity up to 6.96 × 10 10 Jones, which are superior compared with previous work. A higher photo-responsivity (∼170 A W −1 ) communication band (1310 and 1550 nm) is realized for graphene/C60 /Bi2 O2 Se than for previous related work. The coupling energy bands of Bi2 O2 Se and C60 were determined by first-principles calculation, suggesting two carrier transfer paths into the graphene channel (charge separation and tunneling injection). This was further verified by gate modulation and a control group. This unique photo-response phenomenon and high-performance phototransistor will enable next-generation large-scale array optical imaging and provide a valid platform for exploring communication band applications and polarity converting of photocurrents.